(untitled) (Archive of Conferences, 2021)
People usually start looking for the meaning of names that are incomprehensible to them and try to pronounce by adapting them to their own language. Folk etymology, more precisely false etymology, appears in this way, and thus legends are also made up. In this article, it is mentioned about ethnotoponomics and the designation of historical names